Biologically active supplements overview: regulation, market trends, application, and health impact - A. M. Stepanova; A. N. Plutnitskiy; E. V. Gameeva (Фармакоэкономика, 2024)
The use of biologically active supplements (BAS) has gradually expanded over the past 20 years. The public health crisis caused by the COVID-19 pandemic as well as concerns about vaccines in many parts of the world have led to a particularly increased interest in using BAS as an alternative for protection and treatment of this new disease to strengthen the immune system and minimize the risk of possible complications. Abroad, as well as in the Russian Federation, there is a sharp increase in BAS sales. In this regard, questions arise about their impact on human health in general. Numerous scientific studies have demonstrated both the beneficial properties of BAS and their negative and even toxic effects. Besides, considering the global interest in this problem, there is a need to clarify the legal status of BAS. The object of this review was to summarize the available foreign data on the regulation of using BAS and the corresponding market trends, including a comprehensive analysis of the legislative and regulatory aspects of BAS in the United States, China, and the European Union. The structure and volume of the BAS market were assessed in countries, which primarily produce and import them, and the user profile was analyzed additionally.